Access to, use of, and experiences with social alarms in home-living people with dementia: results from the LIVE@Home.Path trial - Puaschitz, Nathalie Genevieve Søyland; Jacobsen, Frode Fadnes; Berge, Line Iden; Husebo, Bettina Sandgathe (Frontiers in Aging Neuroscience, 2023)
Background: Social alarms are considered to be an appropriate technology to secure safety and independence in older adults, but limited research has been conducted into the actual use of it. We therefore explored the access, experiences, and use of social alarms in home-dwelling people with dementia and their informal caregiver (dyads). Methods: During May 2019 to October 2021, the LIVE@Home.Path mixed-method intervention trial collected data from semi-quantitative questionnaires and qualitative interviews conducted among home-dwelling people with dementia and their informal caregivers in Norway. The study focused on data from the final assessment at 24 months. Results: 278 dyads were included, and 82 participants reached the last assessments. The patients’ mean age was 83 years, 74.6% were female, 50% lived alone, and 58% had their child as caregiver. Totally 62.2% had access to a social alarm. Caregivers answered more often that the device was not in use (23.6%) compared to the patients (14%). Qualitative data revealed that about 50% of the patients were not cognizant of having such an alarm. Regression analyses assessed that access to a social alarm was associated with increased age (86-97 years, P=0.005), and living alone (P<0.001). Compared to their caregiver, people with dementia more often answered that the device gave them a false sense of safety (28% vs. 9.9%), while caregivers answered more often that the social alarm did not give them any value (31.4% vs.14.0%). The number of installed social alarms increased from 39.5% at baseline to 68% at 24 months. The frequency of unused social alarms increased from 12 months (17.7%) to 24 months (23.5%), and patients felt safe less often during that period (60.8% vs. 70%). Conclusion: Depending on their living situation, patients and relatives experienced the installed social alarm differently. There is a gap between the access to and the use of social alarms. The results indicate an urgent need for better routines in the municipalities with regard to offering and following-up existing social alarms. To meet the users’ changing needs and abilities, passive monitoring may help to adapt to declining cognitive abilities and increase their safety. Clinical trial registration: ClinicalTrials.gov, NCT04043364.